Factors affecting the selection of Kadazandusun ethnic foods among students of Universiti Malaysia Sabah, Malaysia - Adilah Md Ramli; Dg Khairunisa Ahmad Sapawi; Shalawati Ibrahim; Saw Chin Weon (Hasanuddin University, Faculty of Law, 2023)
Ethnic food refers to food originating from a specific ethnic group. The study identifies the knowledge and factors in Kadazandusun ethnic food selection among students at the Universiti Malaysia Sabah (UMS). A total of 410 students from Universiti Malaysia Sabah were recruited as respondents through the snowball method. This quantitative study used questionnaires to collect data. The closed-ended questionnaire has four parts: demographics, knowledge, factors affecting food selection, and Kadazandusun ethnic food consumption intention. Data were analyzed using descriptive statistics and presented as frequencies, percentages, and mean values to address the study aims. In this study, 46.8% of the respondents had low knowledge (scale of 0–50) about Kadazandusun ethnic food. As factors that influence food selection, the health factor with an average value of x= 3.39 ± 1.095 received a neutral response toward agreeing compared with the convenience factor (x= 3.17 ± 1.086), taste/sense of food (x= 3.12 ± 1.170), price (x= 3.17 ± 1.134), and habit (x= 2.55 ± 1.164). Therefore, awareness and ethnic food selection factors among students are still low. A mechanism that can promote ethnic food, especially among IPTA students, for sustainability, information dissemination, and consumption of traditional ethnic food, is needed so that it does not disappear.